Becoming a Climate Change Educator: First-grade Pupils’ Action Research - Sandra Kairė; Jovita Vaivadaitė; Augustina Kundrotaitė (Acta Paedagogica Vilnensia)
This paper presents the results of the action research conducted by the research team in 2022-2023 with first-grade pupils at one Vilnius primary school in Lithuania. Primary, the action research aimed to improve the teaching practice of a primary school teacher on the topic of climate change and also develop her professional competence in climate change education; secondary, stimulate the learning process and possible actions for first-grade children on tackling climate change. The study reveals the learning process of the primary school teacher who integrated a series of 14 climate change lessons the research team created, her learning outcomes, and the main challenges she faced during the process. The results highlight specific changes that are taking place in the teacher‘s daily practice that are also undoubtedly leading to an increase in first-grade pupils‘ awareness of climate change topics. The study highlights a key aspect: becoming a climate change educator means developing her professional competence to work on climate change and developing a personal relationship with climate change phenomenon that moves beyond the classroom environment. The development of a personal relationship with climate change brings to the forefront the teacher‘s awareness of the need for climate change education at school to reduce the destructive activities of human beings in relation to the planet and mitigate the effects of human-induced climate change.